(3GdSHYjGJ aj ehGYX GdHQjGJs - (3GdgeOGfj, Yjf GdbVGI, eMeO Hf YHO GdMj, J HYO (B966(3g`s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdLHGQ bGd CHh fUQ eMeO Hf YHO GdQMef GdgeOGfj CYde Cf GdNGdb GdHGQj LdJ bOQJg Rjf GdCTjGA GdSHYI HGdCTjGA SHYIs
(3BNQgG (B:s
(3aCYWjJ GdLeYI hGdLfI dCeJc hQVGFj eY GdLeYI hGdLfI gOjI dges
(3fSNJ gPg GdfSNI ef fSNI Ydj LdHjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 195s
(3eYLe GdeDdajf(B: 3 / 403s
(3cTa GdXfhf(B: 2 / 977s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs